MUSEUM NASIONAL PROGRAM “BELAJAR MENARI” ONLINE DURING THE COVID-19 PANDEMIC THROUGH INSTAGRAM - Fitria Ayuningtyas; Uljanatunnisa Uljanatunnisa; Luqman Hakim; Drina Intyaswati; Witanti Prihatiningsih (Universitas Djuanda Bogor, 2023)
Museums are the most representative example of cultural production. Although social media has triggered the attention of scholars, no previous study has classified the main ways in which social media affect museums. Museums must adapt to changing practices and technologies to remain relevant in society. Meanwhile, no transformation has been more visible than the emergence of digital technology such as social media. To preserve Indonesia's indigenous culture, Museum Nasional held a program called “belajar menari” online. This was done online due to the Covid-19 pandemic which not only hit Indonesia but also the world. In Indonesia, during covid-19 pandemic, society is required to #stayathome by the Government. To find out how the contents of the Museum Nasional’s Instagram became an e-publication, the researchers compiled data about the museum program “belajar menari” online during July to September 2021 period. The research aimed to explore Instagram content as a medium of historical education. To define the message's features, a qualitative descriptive content analysis was used as the research approach. The result of this research indicated that this program can indirectly increase the sense of nationalism as well as preserve Indonesian culture.